QUAN TRẮC NỒNG ĐỘ VÀ PHÂN TÍCH ĐẶC TÍNH CỦA BỤI MỊN TẠI PHƯỜNG LONG BÌNH, THÀNH PHỐ BIÊN HÒA, TỈNH ĐỒNG NAI - Bùi, Duy Linh; Hoàng, Anh Lê; Nghiêm, Xuân Trường; Nguyễn, Thanh Tuấn; Lê, Bảo Hưng; Nguyễn, Đức Thắng; Phạm, Thu Huyền (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
EVALUATION OF PM2.5 MASS CONCENTRATION AND ITS CHEMICAL PROPERTIES ON LONG BINH WARD, BIEN HOA CITY DONG NAI PROVINCEAir pollution is one of the environmental problems, especially pollution caused by fine particulate matter PM2.5. the air quality is affected by many industrial parks distributed in Bien Hoa city, and also by neighbouring areas such as Binh Duong province and Ho Chi Minh city. This study evaluated the distribution of PM2.5 concentrations, which were collected in Long Binh ward, Bien Hoa city, Dong Nai province, and its chemical properties. PM2.5 samples were analyzed for the chemical composition of 11 metal elements (As, Pb, Mn, Fe, Cd, Cr, Zn, Co, Al, Cu, Ni) by ICP - MS/ICAP RQ equipment. The results were collected from 10 samples of PM2.5 in October 2021. The average daily value of PM2.5 concentration ranges from 21.6 µg/m3 to 101.6 µg/m3, with the average value is 40.9 µg/m3 ± 23.6 µg/m3. The results of the analysis of 11 metals showed that the average concentration of Fe, Zn, Cu, Al in this group ranged from 0.12 µg/m3 - 0.41 µg/m3. Through the calculation of the enrichment coefficient, it was also determined that 7/10 elements have been strongly affected by human activities.